-1+8m=-15-6m

Simple and best practice solution for -1+8m=-15-6m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -1+8m=-15-6m equation:



-1+8m=-15-6m
We move all terms to the left:
-1+8m-(-15-6m)=0
We add all the numbers together, and all the variables
8m-(-6m-15)-1=0
We get rid of parentheses
8m+6m+15-1=0
We add all the numbers together, and all the variables
14m+14=0
We move all terms containing m to the left, all other terms to the right
14m=-14
m=-14/14
m=-1

See similar equations:

| 7p+8p-1=59 | | 4x–15=7x | | a=3400+600+21000 | | 5(w-11/10)=-82/5) | | 8x(M)=4 | | c-3.48=0.23 | | 132=-3-9n | | 15x+150=600 | | -6=(2a) | | 43x+14=86 | | (19x+8)-(7x+10)=22 | | (6x-5)+4x-6)=12 | | -50=-10(s+6) | | 2k+9=k+3 | | 2(x-3)+1=5x-3(1+x) | | 5-6x-10=-5-6x | | 136=-8b | | 2(3x-1)=82 | | a=3(a-3)+15+2a+9 | | y-16=47 | | 8^7x=512 | | 5p+4=6p-1 | | 3x+3+4x=2x | | 7x-36=-56 | | 2v=6v+7v | | 4x-40=118 | | 15x-3(3x+4)=7(x=-4) | | -2.2=v/7+15.3 | | 5x-2(2x+6)=12 | | |–x|=–7 | | 10x-4x+2x=24 | | n+0.65=0.793 |

Equations solver categories